Perjanjian Nuklir Iran dan Pengaruhnya terhadap Kepentingan USA-Israel di Timur Tengah - Kiki Mikail (Jurnal ICMES, 2018)
The aim of the research is to expalin about USA-Israel political strategy to the midlle east countries. After 39 years the victory of Islamics Revolution in Iran, Iran become a influential state, particularly in the Midlle East. Iranian military protecting against Israel military oppresion to the midlle east countries such Lebanon, Syiria and Palestine, Iran become an important partner for some midlle east countries in one side, and become an enemy for Israel and ally in other side. Substitution of the USA president from Barack Obama to Donald Trump after the election, is the most dramatic Presidential Election in USA President Election history Iran nuclear deal wich famous by JCPOA name almost final and finish during Barack Obama Presidency, has been used as Israel momentum to attack Iran and ask USA and allies to pressure Iran and considering new penalties and seek to punish several companies and individuals from Iran and the United States has imposed several new non-nuclear sanctions against Iran. However, Europe Union particularly France, Germany and United Kingdom have a strategic interest in depending the Iran nuclear deal. Bussines relation have been signed between Iran Goverment and several Europe Union companies and the EU concerned soaring the global oil prices, forcing the EU to think hard how to keep JCPOA even though the USA is out of from JCPOA.